TAMAN WORKSHOP TAMBANG INTAN MODERN DI CEMPAKA - Khairani Khairani; Mohammad Ibnu Saud (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2021)
Banjarbaru City is one of the areas in South Kalimantan which is widely known to the public as a diamond-producing area. Many wilah in the city of Banjarbaru that are used as mining locations, PT Galuh Cempaka is one of them. At PT Galuh Cempaka's diamond mine, there are many abandoned diamond mining equipment that will eventually become a pile of scrap metal. The workshop equipment still has an economic and aesthetic selling point. In this case, it becomes interesting to develop a tourist attraction with the concept of a workshop equipment park. So that we need a place that can provide information for the community to raise awareness of the negative impacts of mining. To realize the development of a diamond mining workshop, PT Galuh Cempaka Banjarbaru has become a memorial park that can provide information on the negative impacts of mining. Layering method is used with the principle of superimposition to accumulate special interest tourism activity programs and information galleries.